Giant Fibroelastoma of the Aortic Valve - Michele di Summa; Federica Iezzi (Case Reports in Cardiology)
Fibroelastomas account for less than 10% of all cardiac tumours, representing the most common valvular and the second most common cardiac benign tumour, following myxomas. Fibroelastomas are histologically benign; they can result in life-threatening complications such as stroke, acute valvular dysfunction, embolism, ventricular fibrillation, and sudden death. Surgical resection should be offered to all patients who have symptoms and to asymptomatic patients who have pedunculated lesions or tumors larger than 1 cm in diameter. Valve-sparing excision produces good long-term results in most instances. We report our surgical experience of a giant fibroelastoma in the aortic valve.